The Cambridge handbook of investor protection / edited by Arthur B. Laby. - Laby, Arthur B. (Cambridge University Press, 2022)
The topic of investor protection has occupied investors, businesses, regulators, academics, and courts since the 1930s. The topic exploded in importance after the 2008 financial crisis and the Bernard Madoff Ponzi scheme of the same year. Investor protection scholarship now seeks to respond to developments such as the institutionalization of the markets, the democratization of finance, and the enhanced role of market professionals and other gatekeepers. Additionally, although the philosophy of full disclosure remains the guiding principle behind the securities laws, recent research has questioned the merits of a disclosure-based regime. In light of these trends, regulators try to strike the right balance between imposing a strict investor protection regime, on the one hand, and giving businesses the freedom to innovate new projects, market new services, and reduce costs, on the other. The Cambridge Handbook of Investor Protection brings together leading scholars to inform this debate and fill a gap left by these developments.